Predisposing Factors for Infantile Urinary Calculus in South-West of Iran (Iranian Journal of Kidney Diseases, 2014)
Introduction. Urinary calculi in infants are relatively infrequent, but their incidence has increased in the recent decades. The aim of this study was to investigate the clinical presentation, metabolic risk factors, and urinary tract abnormalities in infants suffering from kidney calculus. Materials and Methods. A total of 152 infants were admitted between 2009 and 2012 with ultrasonography-proven urolithiasis. A Foley catheter was fixed and 24-hour urine samples were analyzed for calcium, citrate, oxalate, uric acid, and magnesium. For detecting cystinuria, qualitative measurement of urinary cystine was done by nitroprusside test. Urinary tract structural abnormalities were also evaluated. Results. The mean age at the diagnosis of kidney calculus was 5.46 months (range, 15 days to 12 months). The most common clinical findings were restlessness and urinary tract infection. A family history of calculi was found in 67.1% of the patients and 68.4% were born to consanguineous marriages. Metabolic abnormalities and urinary tract abnormalities were found in 96.1% and 15.1% of children, respectively. Urinary tract abnormalities were more common in girls. The most common metabolic risk factors were hypercalciuria (79.6%) and hypocitraturia (40.9%). Hyperoxaluria and hypomagnesuria were found in about 28% of patients, both of which were associated with bilateral urolithiasis. Conclusions. These findings show that urinary metabolic abnormalities are very common in infants with urolithiasis. Appropriate evaluation of urinary metabolic parameters can lead us to proper diagnosis and treatment.